Transformation of a Malaysian species of Nannochloropsis: gateway to construction of transgenic microalgae as vaccine delivery system to aquatic organisms. Issue 1 (1st January 2020) - Zainal Abidin, Aisamuddin Ardi; Suntarajh, Mohanrajh; Balia Yusof, Zetty Norhana
ABSTRACT: Nannochloropsis: sp. is a green alga that is widely used in the aquaculture industry as a feed in Malaysia, but genetic engineering studies of this alga are still underexplored even though there is a growing interest in microalgae genetic engineering for various industrial purposes. This study aims to investigate the efficiency of three transformation methods normally done on microalgae, namely polyethylene glycol (PEG), electroporation, and glass beads on Malaysian indigenous Nannochloropsis sp. using two commercially available plasmids, pUC19 and pGEM-T easy vector as well as an amplicon of ampicillin resistance (AMPR) gene. In this study, out of three transformation methods tested, positive transformants of Nannochloropsis sp. were successfully obtained via electroporation method. Further verification via polymerase chain reaction (PCR) and sequencing confirmed that the electroporation method was found to be the sole successful method in producing transgenic lines of our locally isolated Nannochloropsis sp. Results from this study proved the efficiency of electroporation for delivery of transgene to this green alga which has been reported to be tedious. The described method also provides the gateway for developing Nannochloropsis sp. as a delivery system to aquatic organism due to its importance in the industry. Graphical abstract: